2019
DOI: 10.1590/1983-21252019v32n305rc
|View full text |Cite
|
Sign up to set email alerts
|

EXOTIC ARBUSCULAR MYCORRHIZAL FUNGI AND NATIVE DARK SEPTATE ENDOPHYTES ON THE INITIAL GROWTH OF Paspalum millegrana GRASS

Abstract: Arbuscular mycorrhizal fungi (AMF) and dark septate endophytic fungi (DSE) promote increase in plant biomass, depending on the soil and climate conditions and the interactions with the host plant. The objective of this study was to evaluate the interaction of exotic arbuscular mycorrhizal fungi and native DSE fungi on the initial growth of P. millegrana. A completely randomized experimental design comprising the Paspallum millegrana cutilvar with the following treatments: control - without AMF, and three exoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
1
0
3
Order By: Relevance
“…This negative effect on DSE colonisation has been evidenced by other studies [148][149][150]. However, other studies have revealed positive effects showing an increase in DSE colonisation [111,151,152], or neutral effects, wherein the colonisation rates of both the co-inoculants were unaffected [111,[153][154][155][156]. Table 2 lists various studies on the compatibility between DSEs and other microorganisms.…”
Section: Compatibility Of Dses With Other Microorganismsmentioning
confidence: 72%
“…This negative effect on DSE colonisation has been evidenced by other studies [148][149][150]. However, other studies have revealed positive effects showing an increase in DSE colonisation [111,151,152], or neutral effects, wherein the colonisation rates of both the co-inoculants were unaffected [111,[153][154][155][156]. Table 2 lists various studies on the compatibility between DSEs and other microorganisms.…”
Section: Compatibility Of Dses With Other Microorganismsmentioning
confidence: 72%
“…A taxa de colonização micorrízica foi realizada aos 14, 28 e 42 dias da semeadura pelo método de intersecção desenvolvido por Giovannetti e Mosse (1980) e modificado por Mendonça et. al.…”
Section: Crescimento Das Mudas Do Tomateiro Ipa06 Com Isolados Micorr...unclassified
“…A ocorrência dos fungos DSE pode ter sido oriundo das sementes, tal como observado em arroz por Gois et al (2019) ou devido a não desinfestação do substrato orgânico utilizado no cultivo, à base de terra vegetal e pó de coco. Pois, Rieth (2012), ao pesquisar o desenvolvimento de porta-enxertos de citros com fungos micorrízicos, em diferentes substratos, recomendou a desinfestação de substratos orgânicos.…”
Section: Crescimento Das Mudas Do Tomateiro Ipa06 Com Isolados Micorr...unclassified
See 1 more Smart Citation